Interspatial gender asymmetries in early Soviet Siberia - Sablin, Ivan; Savelʹeva, Marija Sergeevna (Gender, place and culture, 2015)
The article addresses gendered power asymmetries within indigenous communities of early Soviet Siberia and their shifts during the transitional period between the Russian Empire and the totalitarian Soviet state. The concept of entangled relational spaces is the main analytical tool of this article. Seeking to overcome identity-based essentialisms, the article deconstructs gender identity and demonstrates how it can be articulated and interpreted in different relational spaces. It extends the argument that oppressions are produced by various social categories (intersectionality) by adding that a single social category may beget various forms of oppression and that heterogeneous gender asymmetries are produced and manifested across different relational spaces. Evidence deriving from predominantly indigenous sources authored by women enabled the discussion of gendered power asymmetries in economic, legal, and political spaces produced by corresponding relations. Economic and demographic crises, which the indigenous peoples of Siberia endured in the 1910s-1920s, reduced gendered power asymmetries in economic spaces making women less dependent on men. On women's initiative the shifts then spread to legal spaces and, with the support of the Bolshevik government, affected political spaces. These shifts were closely connected to the early Soviet attempts at dialog with indigenous people, decolonizing Siberia and liberating indigenous women, and gave way to instrumental policies.